Lipoprotein (a) as a risk factor of ischemic stroke: a case-control study - More, Prashant Pramod; Itkelwar, Bhushan Jayant; Patil, Dilip Ratan (International Journal of Advances in Medicine, 2017)
Background: Undoubtedly, stroke is an important public health problem as well as an important precursor of mortality and morbidity. It also leads to loss of disability adjusted life years as it causes long term severe disability. The objective of this study was to study association of lipoprotein (a) in ischemic stroke patients with matched controls. Methods: This is a prospective case controlled study. The study group includes 100 stroke patients consecutive admitted in medicine/neurology departments of our hospital, and 50 patients as control group admitted for nonvascular diseases. The ethical committee clearance was obtained from the appropriate authority appointed by the institution. Detailed history taking and neurological examination were done in all patients Results: This case-control study shows that ischemic stroke patients have higher levels of Lp (a) as compared to that of controls. Thus, people with high Lp (a) levels may have higher predilection for developing ischemic stroke. Lp (a) levels do not correspond to stroke severity stroke in our study. Thus, higher Lp (a) levels do not lead to more severe type of stroke. Lp (a) levels do not correlate with the outcome of stroke, hence Lp (a) level may not be a good indicator for assessing prognosis or predicting mortality Conclusions: This case-control study shows that ischemic stroke patients have higher levels of Lp (a) as compared to that of controls. Thus, people with high Lp (a) levels may have higher predilection for developing ischemic stroke factors for stroke like diabetes, smoking and hypertension do not predisposed to higher Lp (a).